The Analysis of Determinants Affecting Patient Waiting Time Perception: The Outpatient Pharmacy Installation of Hospital X Bekasi City Indonesia - Nirmala Nirmala; Purwanti Aminingsih; Enrico Adhitya Rinaldi (CV. Inara, 2026)
Waiting time in pharmacy services is one of the key indicators of hospital service quality that influences patient satisfaction and perception. Perceived waiting time is not solely determined by the actual duration of service but is also affected by operational and psychological factors experienced by patients during the waiting process. This study aims to analyze the influence of service process efficiency, pharmacists’ communication, waiting room comfort, and drug availability on patients’ perceived waiting time at the Outpatient Pharmacy Installation of RS X, Bekasi City Indonesia. This study employed a quantitative approach with a cross-sectional design. The population consisted of outpatients who redeemed prescriptions at the pharmacy installation, and samples were selected using an accidental sampling technique. Data were collected through a structured questionnaire that had been tested for validity and reliability. Multiple linear regression analysis was used to determine both partial and simultaneous effects among variables. The results indicate that service process efficiency, pharmacists’ communication, waiting room comfort, and drug availability have a significant partial effect on patients’ perceived waiting time (p < 0.05). Simultaneously, all four variables also significantly influence perceived waiting time. Service process efficiency was identified as the most dominant factor affecting patients’ perceptions. These findings suggest that improving pharmacy service quality requires a comprehensive strategy, including workflow optimization, enhancement of pharmacists’ communication skills, improvement of waiting room facilities, and strengthening drug inventory management to create a better patient service experience.